Alcance y límites de la potencia humana - Donadío Maggi de Gandolfi, María C. (Sapientia, 2012)
Man’s view of his manner of being conditions his acting in the world in one way or another. Generally speaking, this is a starting point shared by the different currents of philosophical thought when it comes to giving an answer to the exercise of human potential despite the fact that these can differ greatly as to how to explain the passage of being-acting. In this sense, among the explanations, which are the farthest from each other, it is important to consider, on the one hand, a conception which relies on metaphysical realism and recognizes the dialectic of participation and, on the other, a conception which claims to be anti-metaphysical by diluting being in its denial, in the nothingness, thus exalting man’s will power. Although this work will be developed following the former, from the study of causation of the act of being in Tomas Aquinas, I shall draw on the latter, namely Nietzschean nihilism, but solely as a way of establishing the status quaestionis, seeking to remove critically a recurrent objection throughout the history of thought on the scope and limits of human operation.